Pregnancy-Induced Changes in microRNA Expression in Multiple Sclerosis - Sondergaard Helle Bach; Airas Laura; Christensen Jeppe Romme; Nielsen Birgitte Romme; Bornsen Lars; Oturai Annette; Sellebjerg Finn (FRONTIERS MEDIA SA, 2025)
Pregnancy affects the disease course in multiple sclerosis (MS), particularly in the third trimester, where the relapse rate is reduced by as much as two thirds. This study aimed at identifying changes in microRNA (miRNA) and immune cell phenotypes in pregnant MS patients. Discovery and validation studies to detect differentially expressed miRNAs were performed with quantitative real-time PCR on peripheral blood mononuclear cells (PBMC). Flow cytometry analysis was performed on PBMC stained with antibodies directed against surface markers of antigen presenting cells (APCs), NK-cells, NKT cells, CD4+ and CD8+ T cells and subsets of these cell types, including PDL1 and PDL2 expressing subsets. RNA was extracted from whole blood, monocytes, and NK-cells to investigate expression and correlation between regulated miRNAs and mRNAs. In total, 15 miRNAs were validated to be differentially expressed between third trimester pregnant and postpartum MS patients (Benjamini-Hochberg false discovery rate from p = 0.03-0.00004). Of these, 12 miRNAs were downregulated in pregnancy and 6 of the 15 miRNAs were altered by more than +/- 2-fold (+2.99- to -6.38-fold). Pregnant MS patients had a highly significant increase in the percentage of monocytes and a decrease of NK-cells and myeloid dendritic cells compared to non-pregnant MS patients. We confirm previous reports of a relative increase in CD56-bright NK-cells and a decrease in CD56-dim NK-cells in third trimester of pregnancy and report an increase in non-committed follicular helper cells. PDL1 and PDL2 expression was increased in pregnant patients together with IL10. Also, in monocytes IL10, PDL1, and PDL2 were upregulated whereas miR-1, miR-20a, miR-28, miR-95, miR-146a, miR-335, and miR-625 were downregulated between pregnant and untreated MS patients. IL10, PDL1, and PDL2 were predicted targets of MS pregnancy-changed miRNAs, further supported by their negative correlations. Additionally, previously identified pregnancy-regulated mRNAs were identified as predicted targets of the miRNAs. PDL1 and PDL2 bind PD-1 expressed on T cells with an inhibitory effect on T-cell proliferation and increase in IL10 production. These results indicate that some of the effects behind the disease-ameliorating third trimester of pregnancy might be caused by changed expression of miRNAs and immunoregulatory molecules in monocytes.